The increase of asthma self-medication in Indonesia during COVID-19 Pandemic: An infodemiology study using Google Trends - Setiawan, Hendri; Rahmah, Atika; Hartanto, Nadira Rachmianti; Awanis, Ghina Shabrina (Universitas Udayana, 2024)
Background and purpose: The COVID-19 pandemic has significantly interrupted the care of asthma patients. In order to determine whether online search data and the number of COVID-19 cases were related, many Google Trends-based investigations were carried out throughout the pandemic. This study investigates whether asthma patients use the internet for self-management and treatment advice. Methods: A netnographic approach with data sources from Google Trends was used in our research. The data were taken from www.https://trends.google.co.id and were collected within two timeframes: (1) the beginning of COVID-19 (March 2, 2018-March 1, 2020) and (2) during the pandemic COVID-19 (March 2, 2020-March 1, 2022). The data is displayed graphically on a scale of 0 to 100, referred to as the Relative Search Volume (RSV). The Spearman correlation test on each keyword and the confirmed cases of COVID-19 in Indonesia were done in SPSS version 25 (IBM Corp., Armonk, NY) to determine if a correlation existed. Results: This study found an increased search volume for asthma therapy. According to the correlation test results, the keywords